In vivo tumor identification of colorectal liver metastases with diffuse reflectance and fluorescence spectroscopy. Issue 9 (8th September 2016) - Tanis, Erik; Evers, Danny J.; Spliethoff, Jarich W.; Pully, Vishnu V.; Kuhlmann, Koert; van Coevorden, Frits; Hendriks, Benno H.W.; Sanders, Joyce; Prevoo, Warner; Ruers, Theo J.M.
Abstract : Background and Objective: Over the last decade, an increasing effort has been put towards the implementation of optical guidance techniques to aid surgeons during cancer surgery. Diffuse reflectance spectroscopy (DRS) and fluorescence spectroscopy (FS) are two of these new techniques. The objective of this study is to investigate whether in vivo optical spectroscopy is able to accurately discriminate colorectal liver metastases (CRLM) from normal liver tissue in vivo . Materials and Methods: DRS and FS were incorporated at the tip of a needle and were used for in vivo tissue differentiation during resection of CRLM. Measurements were taken in and around the tumor lesions and measurement sites were marked and correlated to histology (i.e., normal liver tissue or tumor tissue). Patients with and without neoadjuvant systemic chemotherapy were included into the study. Results: Four hundred and eighty‐four measurements were taken in and near 19 liver lesions prior to resection. Overall sensitivity and specificity for DRS was 95% and 92%, respectively. Bile was the most discriminative parameter. The addition of FS did not improve the overall accuracy. Sensitivity and specificity was not hampered by neo‐adjuvant chemotherapy; sensitivity and specificity after neo‐adjuvant chemotherapy were 92% and 100%, respectively. Conclusion: We have successfully integrated spectroscopy technology into a disposable 15 Gauge optical needle and we have shown that DRS and FS can accurately discriminate CRLM from normal liver tissue in the in vivo setting regardless of whether the patient was pre‐treated with systemic therapy. This technique makes in vivo guidance accessible for common surgical practice. Lasers Surg. Med. 48:820–827, 2016. © 2016 Wiley Periodicals, Inc.